Analyzing the major ions and trace elements of groundwater wells in Kuala Langat, Selangor - Haspi Harun, Hazimah; Mohamad Kasim, Mohamad Roslan; Abu Bakar, Siti Nurhidayu; Asha’ari, Zulfa Hanan; Mohd Kusin, Faradiella (Penerbit UTM Press, 2021)
The analysis of trace elements and major ions on groundwater wells in Kuala Langat become the aim of this paper for the purposes to investigate the quality of the groundwater to be considered as a suitable alternative water source for domestic purposes. The groundwater sampling was conducted in thirteen stations of groundwater wells. The groundwater samples were taken from the groundwater wells which scatter in agricultural areas in Kuala Langat, Selangor. The major ions parameters have analyzed in the groundwater samples were calcium, magnesium, potassium, bicarbonate, chloride, and sulfate (Ca2+, Mg2+, K+, Na+, HCO3 -, Cl-, SO4 2-). Meanwhile, the trace element parameters were aluminum, iron, manganese, strontium, zinc, and copper (Al, Fe, Mn, Sr, Zn, and Cu). Principal Component Analysis (PCA) was conducted to determine the influence of major ions and trace elements concentration in groundwater. Chloride, potassium, magnesium, strontium, calcium, and bicarbonate (Cl-, Na+, K+, Mg2+, Sr2+, Ca2+, and HCO3 -) were principal parameters in the first component of PCA analysis. The concentration of trace elements shows iron is the high concentration in groundwater samples. Hence, the concentration of iron in current sampling shows exceed the recommended level for raw water of the Ministry of Health. The influences from seawater intrusion and Sodium Adsorption Ratio (SAR) in groundwater also have been discussed.